2021
DOI: 10.3390/ijerph18062941
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Time of Eating in Commensality Research

Abstract: Commensal meals seem to be related to a better nutritional and metabolic health as well as an improved quality of life. The aim of this paper was to examine to what extent research was performed using the search term commensality related to assessment of timing of meals. A scoping review was performed, where 10 papers were identified as specifically addressing the assessment of timing of commensality of meals. Time use studies, questionnaires, and telephone- and person-to-person interviews were used for assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
2
3
0
Order By: Relevance
“…This insight supports the notion that interventions aimed at dietary improvement should be multifaceted, addressing not only the nutritional value of food but also the socioeconomic barriers to healthy eating. This viewpoint aligns with findings from other studies, such as those by , which underscore the importance of social context of diet in assessing nutritional health [33], resonating with our research that highlights the multifaceted nature of food choices. Scander's findings suggest that interventions targeting dietary improvements must consider the broader socioeconomic and cultural factors that influence when and with whom individuals eat [33,34].…”
Section: Discussionsupporting
confidence: 90%
“…This insight supports the notion that interventions aimed at dietary improvement should be multifaceted, addressing not only the nutritional value of food but also the socioeconomic barriers to healthy eating. This viewpoint aligns with findings from other studies, such as those by , which underscore the importance of social context of diet in assessing nutritional health [33], resonating with our research that highlights the multifaceted nature of food choices. Scander's findings suggest that interventions targeting dietary improvements must consider the broader socioeconomic and cultural factors that influence when and with whom individuals eat [33,34].…”
Section: Discussionsupporting
confidence: 90%
“…The public health potential of commensality thus remains an open question, calling for further empirical studies from a variety of angles, disciplines, and geographical and cultural contexts. Moreover, we agree with Scander et al [ 96 , 97 ] that learning more about commensality’s role in food and health requires reliable ways of assessing eating together, for example, as part of studies on dietary intake and meal timing.…”
Section: Questioning Commensalitysupporting
confidence: 91%
“…Konno et al (2017) conducted a two-month experiment involving two families and suggested that remote dining involving elderly parents and their children can increase parents' meal satisfaction. Because of the barriers to co-eating caused by time zone differences (Scander et al, 2021), some studies have focused on asynchronous remote co-eating systems and the interactions therein (Noguchi and Inoue, 2016;Obata et al, 2020).…”
Section: Remote Diningmentioning
confidence: 99%